Peningkatan Kualitas Pembelajaran melalui Pelatihan Penyusunan Perangkat Pembelajaran Kurikulum Merdeka di SMPN 1 Majene - Anaguna, Nursyam; Apriyanto, Apriyanto; Syahrir, Nur Hilal A. (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2024)
A change in curriculum policy to the Independent Curriculum is something new for teachers. There are many teacher needs, especially knowledge and skill competencies in terms of preparing Independent Curriculum learning tools, which have not yet been accommodated. The development of knowledge and skills is very important in order to improve the learning process in accordance with the Independent Curriculum. One effort to develop teachers' pedagogical abilities is through training in preparing Independent Curriculum learning tools. This activity was carried out at SMPN 1 Majene, West Sulawesi, which was attended by 32 teachers. Activity stages include preparation, implementation, evaluation and report preparation. The result of this activity is that the level of teacher satisfaction after implementing the training on developing independent curriculum learning tools is in the very satisfactory category.